Soočanje slovenskih bolnikov s pljučno hipertenzijo in njihovih svojcev z boleznijo - Potočnik, Darja (Rehabilitacija (Ljubljana), 2016)
Background: Pulmonary hypertension is a severe, debilitating disease that is characterised with progressive increase in pulmonary arterial pressure (PAP). It is defined by mean PAP while resting equal or greater than 25 mmHg. Hightened PAP leads to overload and dysfunction of the right ventricle. Eventually, this leads to right-ventricle failure, symptoms and signs of low minute heart volume, hypoxemia and consequently an early death. During intense medical treatment and prolongation of life the patients with PH and their families face various psychosocial difficulties. Beside new regulatory changes and developmental tasks a family with a PH patient must also learn to face and live with an unpredictable future and demanding treatment. Hence, we investigated the response of patients with PH and their families to a lifelong presence of pulmonary hypertension, focusing on the ways of coping with the disease. This topic has not been studied yet, so our study represents the beginning of research of psychosocial aspects of patients with PH in Slovenia.
Keywords: chronic disease; coping with illness; družina; Family; family coping; Hypertension, Pulmonary; kronične bolezni; pljučna hipertenzija; psychology; pulmonary hypertension; soočanje z boleznijo